EFNS/ENS Consensus on the diagnosis and management of chronic ataxias in adulthood. (13th January 2014) - van de, B. P. C.; van, J.; Boesch, S.; Burgunder, J.‐M.; Dürr, A.; Giunti, P.; Klockgether, T.; Mariotti, C.; Pandolfo, M.; Riess, O.
<x xml:space="preserve">Abstract</x> Background and objectives The ataxias are a challenging group of neurological diseases due the aetiological heterogeneity and the complexity of the genetic subtypes. This guideline focuses on the heredodegenerative ataxias. The aim is to provide a peer‐reviewed evidence‐based guideline for clinical neurologists and other specialist physicians responsible for the care of patients with ataxia. Methods This guideline is based on systematic evaluations of the relevant literature and on three consensus meetings of the task force. Diagnosis If acquired causes are ruled out, and if the disease course is rather slowly progressive, a (heredo)degenerative disease is likely. A positive family history gives much guidance. In the case of a dominant family history, first line genetic screening is recommended for spinocerebellar ataxia (SCA) 1, 2, 3, 6, 7 and 17 (level B), and in Asian patients also for dentatorubral‐pallidoluysian atrophy (DRPLA). In the case of recessive disease, a stepwise diagnostic work‐up is recommended, including both biochemical markers and targeted genetic testing, particularly aimed at Friedreich's ataxia, ataxia telangiectasia, ataxia due to vitamin E deficiency, polymerase gamma gene (POLG gene, various mutations), autosomal recessive spastic ataxia of Charlevoix−Saguenay (ARSACS) and ataxia with oculomotor apraxia (AOA) types 1 and 2. If family history is negative, we still advise to screen for the more common dominant and recessive ataxias. In addition, if onset is below 45 years we recommend the full work‐up for recessive ataxias; if onset is above 45 years we recommend to screen for fragile X mental retardation 1 FMR1 premutations (good practice points). In sporadic cases with an onset after 30 years, a diagnosis of multiple system atrophy should be considered (good practice point). In particular the genetic work‐up will change over the upcoming years due to the diagnostic utility of new techniques such as gene panel diagnostics based on next generation sequencing for routine work‐up, or even whole exome and genome sequencing for selected cases. Treatment Some of the rare recessive ataxias are treatable, but for most of the heredodegenerative ataxias treatment is purely symptomatic. Idebenone is not effective in Friedreich's ataxia (level A). Riluzole (level B) and amantadine (level C) might provide symptomatic relief, irrespective of exact etiology. Also, varenicline for SCA3 patients (level B) can be considered. There is level Class II evidence to recommend physiotherapy, and Class III data to support occupational therapy.